Genome-wide identification and expression analysis of the NHX gene family under salt stress in wheat (Triticum aestivum L) - Sharma, Pradeep; Mishra, Shefali; Pandey, Bharati; Singh, Gyanendra (Frontiers in Plant Science, 2023)
Salt stress affects plant growth and development, resulting in the loss of crop yield across the world, and sodium-proton antiporters (NHXs) are one of the genes known to promote salt tolerance in transgenic plants. It has been widely studied in numerous plants; however, not much is known about NHXs in wheat. In this study, we conducted a comprehensive genome-wide analysis and expression profile of NHX genes in wheat under salinity stress. We identified 30 TaNHX genes in wheat based on the Na+/H+ exchanger domain, all but one of which contained an amiloride motif, known for inhibiting Na+ ions in plants. Phylogenetic analysis classified these genes into three classes: 12 were localized in vacuoles, while 18 were in the endoplasmic reticulum and plasma membrane. Promoter analysis revealed stress-related cis-acting elements, indicating their potential role in abiotic stress tolerance. The non-synonymous (Ka)/synonymous (Ks) ratios highlighted that the majority of TaNHX genes experienced robust purifying selection throughout their evolutionary history. Additionally, transcriptomic data analysis and qRT-PCR demonstrated distinct expression patterns for TaNHX genes across various tissues when subjected to salt stress. Additionally, we predicted 20 different miRNA candidates targeting the identified TaNHX genes. Protein-protein interaction prediction revealed NHX6's involvement in the SOS1 pathway, while NHX1 genes exhibited proton antiporter activity. Molecular dynamics (MD) simulations were also conducted to examine the interactions of TaNHX1, TaNHX2, and TaNHX3. These results represent a significant advancement in our understanding of the molecular mechanisms governing Na+ transporters. This may also offer promising avenues for future studies aimed at unraveling the intricate details of their biological roles and applications.